1999
DOI: 10.1002/jlb.65.5.658
|View full text |Cite
|
Sign up to set email alerts
|

Increased neutrophil adherence and adhesion molecule mRNA expression in endothelial cells during selenium deficiency

Abstract: Leukocyte aggregation and activation on endothelial cells (EC) are important preliminary events in leukocyte migration into tissue and subsequent inflammation. Thus, an increase in leukocyte adherence has the potential to affect inflammatory disease outcome. Selenium (Se) is an integral part of the antioxidant enzyme glutathione peroxidase (GSH-Px) and plays an important role in the maintenance of the redox state of a cell. Se supplementation in the bovine has been shown to improve the outcome of acute mastiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…The selectin family of adhesion molecules, including E-selectin and P-selectin, are primarily responsible for the initial phase of the leukocyte adhesion cascade. The Ig superfamily of adhesion molecules includes intercellular adhesion molecule-1 (ICAM1), vascular adhesion molecule-1 (VCAM1), and platelet endothelial adhesion molecule-1 (PECAM1) [24]. The expression of both ICAM1 and VCAM1 increase significantly during inflammation and is involved in the firm attachment of blood leukocytes to vascular endothelial cells [18].…”
Section: Impact Of Reactive Oxygen Species On Immunitymentioning
confidence: 99%
“…The selectin family of adhesion molecules, including E-selectin and P-selectin, are primarily responsible for the initial phase of the leukocyte adhesion cascade. The Ig superfamily of adhesion molecules includes intercellular adhesion molecule-1 (ICAM1), vascular adhesion molecule-1 (VCAM1), and platelet endothelial adhesion molecule-1 (PECAM1) [24]. The expression of both ICAM1 and VCAM1 increase significantly during inflammation and is involved in the firm attachment of blood leukocytes to vascular endothelial cells [18].…”
Section: Impact Of Reactive Oxygen Species On Immunitymentioning
confidence: 99%
“…In goats both random and chemotactic migration of neutrophils in vitro were reduced by Se deficiency (Aziz et al 1984). Recently, bovine mammary endothelial cells grown in Se-deficient cell culture media were found to exhibit enhanced neutrophil adherence when stimulated with TNF-α and IL-2 (Maddox et al 1999). This factor could affect neutrophil migration into tissues and subsequent inflammation.…”
Section: Phagocytic Functionmentioning
confidence: 99%
“…Indirectly, ROS can damage cellular components and membranes and thus modify metabolic pathways [22]. Oxidative stress can enhance the adhesion of activated neutrophils to mammary endothelial cells and intensify inflammation [23]. Several studies have shown that supplementing dairy cows with an adequate level of antioxidants increase immune function of cows, i.e.…”
mentioning
confidence: 99%